2014
DOI: 10.1007/s00234-014-1333-3
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy CT for detection of contrast enhancement or leakage within high-density haematomas in patients with intracranial haemorrhage

Abstract: DECT emphasised the iodine enhancement and facilitated the detection of contrast enhancement or leakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The heterogeneity in CTA acquisition protocols [8] with lack of consensus on the optimal CTA setting for spot sign detection may account for this inconsistency. Multiple studies show that scan parameters influence CTA quality and spot sign accuracy in predicting hematoma growth [10, 11, 2022] suggesting the need to harmonize CTA analysis across different centers. The results of our study confirmed the presence of great variability in CTA protocols, and showed that phantom-based iodine calibration may help in standardizing image analysis across multiple sites.…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity in CTA acquisition protocols [8] with lack of consensus on the optimal CTA setting for spot sign detection may account for this inconsistency. Multiple studies show that scan parameters influence CTA quality and spot sign accuracy in predicting hematoma growth [10, 11, 2022] suggesting the need to harmonize CTA analysis across different centers. The results of our study confirmed the presence of great variability in CTA protocols, and showed that phantom-based iodine calibration may help in standardizing image analysis across multiple sites.…”
Section: Discussionmentioning
confidence: 99%
“…15,18,19 It has been shown that by using a combined evaluation of the VNC and IM series from DECT, sensitivity and specificity for the detection of an underlying contrast-enhancing mass within a cerebral hemorrhage was as high as 94.4% and 97.4%, 17 with positive or negative predictive values up to 95.7% and 94.1%. 30 With regard to the differentiation between hemorrhage and contrast staining in different intracranial compartments, another study even described a sensitivity of 100%, specificity between 84.4% and 100%, and accuracy between 87.2% and 100%, with some limitations in calcified areas.…”
Section: Discussionmentioning
confidence: 99%
“…5). 21,24,[28][29][30][31][32][33][34][35][36][37][38][39][40][41] Spectral Hounsfield unit attenuation curves obtained by region of interest (ROI) analysis are a quantitative graphic representation of the energydependent attenuation changes seen on the VMIs (►Fig. 4).…”
Section: Overview Of Different Dect Reconstructions Virtual Monochrommentioning
confidence: 99%